Investigating the Prevalence of the Vancomycin Resistance Gene in Staphylococcus aureus Isolated from Clinical Specimens in Medical Centers in Mazandaran - Fatemeh Nooraei; Mojtaba Mohseni (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Staphylococcus aureus is one of the most important causative agents of infections. The excessive use of antibiotics has led to a rise in antibiotic-resistant strains, including vancomycin-resistant isolates. The aim of this study was to investigate the prevalence of the vanA gene** in S. aureus strains isolated from clinical specimens. Materials and methods: A total of 115 S. aureus isolates were collected from medical diagnostic laboratories and hospitals. The isolates were identified using standard phenotypic methods. The antibiotic resistance profiles of the isolates to commonly used antibiotics were assessed using the disc diffusion method. Vancomycin susceptibility was evaluated using the vancomycin agar screening method, and the minimum inhibitory concentration (MIC) of vancomycin was determined by the agar dilution method. The presence of the vanA gene was detected using polymerase chain reaction (PCR). Statistical analysis was performed using SPSS software, employing Fisher’s exact test and the Mann–Whitney U test. Results: A total of 100 isolates were confirmed as S. aureus. The resistance rates to penicillin, erythromycin, clindamycin, tetracycline, ciprofloxacin, cefoxitin, gentamicin, and rifampin were 90%, 66%, 56%, 54%, 54%, 38%, 4%, and 0%, respectively. The results of vancomycin susceptibility testing, using both phenotypic and genotypic methods, showed that 2% of the isolates were resistant, and 4% exhibited intermediate resistance to vancomycin. Conclusion: The results indicate that the prevalence of resistance genes and the emergence of vancomycin-resistant S. aureus (VRSA) have not changed significantly compared to previous studies. However, given the multidrug resistance of VRSA isolates to many commonly used antibiotics, it is essential to accurately identify and effectively manage infections caused by these strains.